2016
DOI: 10.1136/bmjstel-2015-000090
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomised and blinded comparison of proficiency-based progression full-physics virtual reality simulator training versus invasive vascular experience for learning carotid artery angiography by very experienced operators

Abstract: IntroductionWe assessed the transfer of training (ToT) of virtual reality simulation training compared to invasive vascular experience training for carotid artery angiography (CA) for highly experienced interventionists but new to carotid procedures.MethodsProspective, randomised and blinded.SettingCatheterisation and skills laboratories in the USA.ParticipantsExperienced (mean volume=15 000 cases) interventional cardiologists (n=12) were randomised to train on virtual reality (VR) simulation to a quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…Duarte, Rebelo, and Wogalter (2010) have used VR to develop innovative technologies to improve man-machine interaction and to enhance training performance. Cates, Lönn, and Gallagher (2016) showed that using VR in training can improve performance by 17-49%. Trainees can become easily more familiar with machine operation when the VR training method is used.…”
Section: Introductionmentioning
confidence: 99%
“…Duarte, Rebelo, and Wogalter (2010) have used VR to develop innovative technologies to improve man-machine interaction and to enhance training performance. Cates, Lönn, and Gallagher (2016) showed that using VR in training can improve performance by 17-49%. Trainees can become easily more familiar with machine operation when the VR training method is used.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that VR simulations contribute to enhanced procedural skills, with clear transfer of training to clinical practice [22]. A variety of surgical VR simulators have been developed (e.g., dental, laparoscopic and eye surgery) which have shown clear benefits for medical training [23].…”
Section: Virtual Reality In Health Care Educationmentioning
confidence: 99%
“…There are, as mentioned above, examples of individual projects, but there is a lack of research-based innovation and research on implementation where such solutions are integrated into existing everyday teaching. For example, Cates [22] and Ruthenbeck [23] have requested more research on the use of VR / virtual environments for procedural training at different levels of medical education and exploration of solutions with greater level of interactivity and increased realism.…”
Section: Virtual Reality In Health Care Educationmentioning
confidence: 99%
“…VR technology can change the way that people obtain information, so as to improve the harmony between human and machine and make the human-computer interface more intuitive [1]. VR's immersive and interactive features will play a very important role in improving the testing environment.…”
Section: Introductionmentioning
confidence: 99%